A VDC Framework Proposal for Time Optimization in Diamond Drilling Operations for Mining - Salazar Araujo, Luis Alonso (2023)
A Virtual Design and Construction (VDC) framework proposal is presented for time optimization in diamond drilling operations for a mining exploration project. The mining project is located in the Huancavelica region of Peru and is currently in the underground exploration phase through diamond drilling drillholes. The geology team uses diamond drilling samples to estimate the total mineral reserves of the mine, and they have projected 13,278 meters to be drilled. The VDC framework proposal’s application allowed a better understanding of diamond drilling processes to support the variability source reduction related to equipment, maintenance and operational tasks. The results showed a time optimization in the diamond drilling operation of 10%.